Civic Competencies in Teacher Development among Normal Schools - Tantengco, Nerissa S; Martin, Evangeline L (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: Schools, which cater for children from different cultural backgrounds and cultural heterogeneity, should be regarded as an opportunity venue to emphasize citizenship education. In the context of nation-state in a regional and to contribute to shaping the discourse on emerging ASEAN (Association of South East Asian Nations) identity, a research on competencies in Civic Education is being proposed. With the advent of ASEAN Integration in 2015, South East Asian nations, specially the Philippines, must develop and prepare policy based curriculums and pedagogical approaches appropriate to the level of competencies of students. The research, using the qualitative method, focuses on how competencies of teachers in selected Normal Schools in Civic Education are being developed. This article shows that Civic Education, as a subject, should integrate human rights and peace education, so as to determine how to blend together the particular and the universal, the national and the international, and the individual and the society. A need to support youth-led initiatives and partnerships with civil society is also needed. A need in maintaining stakeholders and actors to be open to different, but effective venues and solutions. Refocusing the minds of the students by stressing that citizens must be aware of their rights and they must also exercise them responsibly to a self-governing, free, and just society.KEW WORD: Citizenship Education; Civic Competencies; Teacher Development; Normal Schools; Civil Society.Â RESUME: âKompetensi Kewarganegaraan dalam Pengembangan Guru di Sekolah-sekolah Keguruanâ. Sekolah, yang diperuntukkan bagi anak-anak dari berbagai latar belakang budaya dan heterogenitas budaya, harus dianggap sebagai wahana untuk menekankan pendidikan kewarganegaraan. Dalam konteks negara-bangsa di suatu kawasan dan untuk berkontribusi dalam membentuk wacana tentang identitas ASEAN (Perhimpunan Negara-negara Asia Tenggara) yang baru, sebuah penelitian tentang kompetensi dalam Pendidikan Kewarganegaraan telah dan sedang diajukan. Dengan dimulainya Integrasi ASEAN pada tahun 2015, negara-negara Asia Tenggara, khususnya Filipina, harus mengembangkan dan menyiapkan kurikulum berbasis kebijakan dan pendekatan pedagogis yang sesuai dengan tingkat kompetensi siswa. Penelitian ini, dengan menggunakan metode kualitatif, berfokus pada bagaimana kompetensi guru di Sekolah Keguruan yang dipilih dalam Pendidikan Kewarganegaraan sedang dikembangkan. Artikel ini menunjukan bahwa Pendidikan Kewarganegaraan, sebagai subjek, harus mengintegrasikan pendidikan hak asasi manusia dan perdamaian, untuk menentukan bagaimana memadukan antara yang khusus dan yang universal, nasional dan internasional, serta individu dan masyarakat. Kebutuhan untuk mendukung prakarsa dan kemitraan yang dipimpin pemuda dengan masyarakat sipil juga dibutuhkan. Kebutuhan untuk mempertahankan pemangku kepentingan dan individu agar terbuka terhadap berbagai tempat dan solusi yang berbeda namun efektif. Memfokuskan kembali pikiran para siswa yang menekankan bahwa warga negara harus menyadari hak-hak mereka sendiri dan mereka harus menjalankannya secara bertanggung jawab dalam sebuah pemerintahan yang mandiri, bebas, dan adil.KATA KUNCI: Pendidikan Kewarganegaraan; Kompetensi Warganegara; Pengembangan Guru; Sekolah Keguruan; Masyarakat Madani.Â Â About the Authors: Nerissa S. Tantengco, Ph.D. is a Full Professor VI in the College of Teacher Development, Faculty of Behavioral and Social Sciences PNU (Philippine Normal University) in Manila, Philippines. Evangeline L. Martin, Ed.D. is currently an Associate Professor IV in the College of Teacher Development, Faculty of Behavioral and Social Sciences PNU in Manila, Philippines. Corresponding authors: tantengco.ns@pnu.edu.phHow to cite this article? Tantengco, Nerissa S. & Evangeline L. Martin. (2017). âCivic Competencies in Teacher Development among Normal Schoolsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.10(1) May, pp.1-18. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of the article: Accepted (August 15, 2016); Revised (December 30, 2016); and Published (May 30, 2017).